Discovery of mutations in Chenopodium quinoa Willd through EMS mutagenesis and mutation screening using pre-selection phenotypic data and next-generation sequencing. (1st April 2019) - Mestanza, Camilo; Riegel, Ricardo; Vásquez, Santiago C.; Veliz, Diana; Cruz-Rosero, Nicolás; Canchignia, Hayron; Silva, Herman
Abstract: Quinoa ( Chenopodium quinoa Willd) is a dicotyledonous annual species belonging to the family Amaranthaceae, which is nutritionally well balanced in terms of its oil, protein and carbohydrate content. Targeting-induced local lesions in genomes (the TILLING strategy) was employed to find mutations in acetolactate synthase ( AHAS ) genes in a mutant quinoa population. The AHAS genes were targeted because they are common enzyme target sites for five herbicide groups. Ethyl methane sulfonate (EMS) was used to induce mutations in the AHAS genes; it was found that 2% EMS allowed a mutation frequency of one mutation every 203 kilobases to be established. In the mutant population created, a screening strategy using pre-selection phenotypic data and next-generation sequencing (NGS) allowed identification of a mutation that alters the amino acid composition of this species (nucleotide 1231 codon GTT→ATT, Val→Ile); however, this mutation did not result in herbicide resistance. The current work shows that TILLING combined with the high-throughput of NGS technologies and an overlapping pool design provides an efficient and economical method for detecting induced mutations in pools of individuals.